2022
DOI: 10.1007/s00127-022-02279-x
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic characteristics associated with parenthood amongst patients with a psychotic diagnosis: a cross-sectional study using patient clinical records

Abstract: Purpose Estimates of parenthood in individuals with psychosis range from 27 to 63%. This number has likely increased due to the introduction of newer anti-psychotics and shorter hospital stays. The problems of psychosis can affect patients’ capacity to offer the consistent, responsive care required for healthy child development. The following research questions were assessed: (1) what proportion of these patients have their children correctly recorded in their clinical notes, (2) what proportion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…While ESM variables are still not as well‐validated as other more traditional psychometric measures, efforts are underway to improve the validity and reliability of ESM measures ( https://osf.io/kg376/ ). Another potential limitation is that many of participants in the sample were married and employed, which is more likely with parents with psychosis (Radley et al, 2022 ), but not representative of the majority of individuals with psychosis (Perälä et al, 2008 ). This may limit the generalizability of these findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While ESM variables are still not as well‐validated as other more traditional psychometric measures, efforts are underway to improve the validity and reliability of ESM measures ( https://osf.io/kg376/ ). Another potential limitation is that many of participants in the sample were married and employed, which is more likely with parents with psychosis (Radley et al, 2022 ), but not representative of the majority of individuals with psychosis (Perälä et al, 2008 ). This may limit the generalizability of these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Between 36% and 44% of people diagnosed with a psychotic disorder are parents (Campbell et al, 2012 ; Radley et al, 2022 ). Parenting is a valued role for people with psychosis (Chernomas et al, 2000 ), but research suggests that the symptoms associated with psychosis may make it more difficult for parents to cope with the daily demands of having children.…”
Section: Introductionmentioning
confidence: 99%
“…Although the precise rate varies from study to study, approximately 50% of women with schizophrenia become mothers, a similar rate to that of women in the general population [6]. Many women with a schizophrenia diagnosis, however, remain unpartnered or live in sequential, unstable relationships, making motherhood doubly difficult [7]. A meta-analysis of 1404 participants in the United Kingdom with a schizophrenia diagnosis (mean age = 39.9), found that only 15.6% were married [8].…”
Section: Complex Decisionsmentioning
confidence: 99%
“…Approximately 440,000 adults in the UK experience psychosis (McManus et al, 2016) and over a third are parents (Radley, Barlow, & Johns, 2022a). Parents who experience psychosis face a multitude of challenges (Campbell et al, 2018), including difficulties in managing responsibilities (Strand et al, 2020), balancing their own and their children's needs (Khalifeh et al, 2009) and relationships (Ackerson, 2003; Gregg et al, 2021).…”
Section: Introductionmentioning
confidence: 99%